Vascular channel reserves in patients with systemic atherosclerosis and type 2 diabetes mellitus - O V Kamenskaya (Endocrinology Research Centre, 2013)
Aims. To determine vascular channel reserves in patients with systemic atherosclerosis and type 2 diabetes mellitus (T2DM). Materials and Methods. Study included 143 patients with systemic atherosclerosis, 40 of them also suffered from T2DM. We applied laser Doppler flowmetry (LDF) to evaluate vascular channel reserves and transcranial spectrometry to assess cerebral oxygenation status. Results. We found that 60% of patients with systemic atherosclerosis and T2DM show microcirculation parameters below critical level, which indicates failure of collateral circulation. This group also showed lower efficiency of cerebral perfusion and more pronounced vascular constriction in response to functional load as compared to diabetes-negative controls. Conclusion. Patients with T2DM, accompanied with systemic atherosclerosis showed lower circulation efficiency and more pronounced autonomous dysregulation of cerebral circulation against patients without diabetes mellitus.